On the lower estimation of the rate of convergence in the local theorem - Gamkrelidze, N. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. Г. Гамкрелидзе. Об одной нижней оценке для скорости сходимости в локальной теоремеN. Gamkrelidzė. Apie vieną konvergavimo greičio apatinį įvertinimą lokalinėje teoremoje